Mother's Knowledge Level About Providing Mp-Asi With Nutritional Status To Babies Aged 6 – 24 Months In Banjarworo Village, Working Area Of Bangilan Puskesmas - SETYORINI, INDAH; Su’udi; Sumiatin, Titik (JOSAR (Journal of Students Academic Research), 2024)
Nutritional knowledge is knowledge related to food that affects a person's nutritional status. Nutritional status is still a major problem in Indonesia with cases of undernutrition and malnutrition in children being found. One of the factors that affect nutritional status is the provision of MP-ASI. This study aims to determine the relationship between mother's level of knowledge about complementary feeding with nutritional status in infants aged 6 – 24 months in Banjarworo Village.The research design used is analytical correlation with a crosssectional approach. The residents of the study are all mothers with 6 – 24 month old babies in the flood Banjarworo village, which number 116 mothers with 90 samples obtained from simple randomly sample collecting techniques. The method of data collection is to distribute questionnaires and analyze using a test correlation spear.The results showed that almost half of mothers who had babies aged 6-24 months in Banjarworo Village had good knowledge of 35 mothers (38.9%) and almost half of infants in Banjarworo Village had poor nutritional status as many as 26 infants (28.9%). From the results of the Spearman Rank Correlation test, it was found that p = 0.004 with p< 0.05 indicating a positive relationship (0.299) between mother's knowledge about complementary feeding and nutritional status in infants aged 6-24 months in Banjarworo Village, Bangilan Health Center working area.Mother's knowledge about good complementary feeding can affect good nutritional status, if given correctly and appropriately. Not only that, mothers can also take part in counseling conducted by cadres to increase knowledge about the provision of MP-ASI with nutritional status in order to increase mother's knowledge about giving MP-ASI.